UJI EFEKTIVITAS NEMATODA ENTOMOPATOGEN (RHABDITIDA: Steinernema DAN Heterorhabditis) SEBAGAI MUSUH ALAMI NON-ENDEMIK PENGGEREK BATANG PADI KUNING (Scirpophaga incertulas) - Chaerani dan Bebet Nurbaeti . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2007)
Efficacy Tests of Entomopathogenic Nematodes (Rhabditida: Steinernema dan Heterorhabditis) as Non-endemic Natural Enemies of Yellow Rice stem Borer (Scirpophaga incertulas). Yellow rice stem borer (Scirpophaga incertulas) is a chronic insect pests of irrigated rice and difficult to control. Entomopathogenic nematodes from the genus Steinernema and Heterorhabditis are promising biological control agents for this pest as their infective juveniles (IJs) are capable of seeking and infecting insect living in moist, cryptic habitat such as galleries created by stem borer larvae. Thirteen indigenous and exotic Steinernema and Heterorhabditis sprayed to rice seedlings in laboratory with nematodes at concentrations of 0.5 or 2.0×104 IJs ml-1 water caused larval mortality between 7–93%. Further test in greenhouse on nematodes that had >50% efficacy showed that an indigenous isolate, H. indicus INA H17, was the most effective among the tested nematodes in killing larvae or pupae (78%). Reduction in plant damage caused by the insects could not be demonstrated as the trials was limited to potted plants. The survival ability of nematodes on rice plants was evaluated by using INA H4 as an example. A low percentage of INA H4 IJs (0.5%) persisted in inner leaf sheath until 7 days post application, while IJs on leaf surface and outer leaf sheath survived only until 2 and 48 hours post application, respectively. Improvement of application strategies including repeated spray, addition of antidessicant and adjusment of spray volume and application at damage threshold or plant critical period are deemed necessary to enhance nematode efficacy and reduce plant damage in the field.